PERBANDINGAN PENGGUNAAN SHOPEEPAY TERHADAP BELANJA ONLINE - Denisa Nopita; Sri Siti Nuraini; Betanika Nila Nirbita (Bisnis-Net, 2023)
ABSTRACTTechnological advances that are developing rapidly have a major impact on behavior patterns in society. As in carrying out daily activities such as shopping, currently many people carry out online shopping activities as a form of technological progress. This research is a quantitative analysis research with a literature review approach. The purpose of this study is to compare the use of ShopeePay to online shopping. The impact of this technological development has also replaced the transaction method with the use of e-wallets, supported by high usage by the public so that business people are aggressively creating various e-wallet applications. Shopee is one of the e-commerce companies that introduces an e-wallet feature called Shoppepay with the aim of providing convenience and providing many benefits so that many people are interested in using ShopeePay. The results of this study are that Indonesian people still use Shoppepay as a transaction tool through the rise of other e-wallets. Shoppe users still use ShopeePay as a transaction tool for online shopping.Keywords: Technology, E-commerce, ShopeePay.